MLI Power Topologies and Voltage Eminence: an Exploratory Review - Rakesh Teerdala (IAES Indonesian Section, 2017)
Due to their performances and inherent edges, particularly in medium-voltage and dynamic applications, multilevel inverters have received associate degree increasing attention in universe industrial applications. This paper deals with a review of the most structure electrical converter topologies additionally their commonest derived and hybrid structures quoted in previous analysis works. It additionally encompasses associate degree investigation on voltage harmonic elimination and THD estimation. For that reason, the paper summarizes the foremost relevant modulation techniques used to date to boost the output voltage quality. Theoretical formulas elicited within the literature, for calculating the output voltage THD higher and lower bounds area unit reportable and verified by adequate simulations.